Stoikisme dalam Kehidupan Bermahasiswa: Menghadapi Tantangan dan Menemukan Ketenangan - Al-Bariq, Akmal; Ichwan, Taufik Nur (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Stoicism is an ancient philosophy that offers a relevant and beneficial life outlook for students in facing the challenges of modern life. This article aims to explain the concept of Stoicism and illustrate how Stoic principles can be applied in the daily lives of students. Through literature review, research methods, and discussions, this article uncovers the benefits and implications of Stoicism in the development of students' quality of life. The research indicates that Stoicism can assist students in dealing with stress, managing emotions, and cultivating a positive and resilient attitude towards academic and social challenges. The conclusion of this article emphasizes the importance of implementing Stoic principles in students' lives as an effective tool for achieving happiness and success.